Managing to improve public services - Jean Hartley, Cam Donaldson, Chris Skelcher and Mike Wallace (CAMBRIDGE UNIVERSITY PRESS, 2008)
This book arises from the bold experiment of the ESRC, supported by the EPSRC, in setting up the Advanced Institute of Management (AIM) research initiative and in particular the funding of 11 Public Service Fellowships. AIM is an innovatory approach to creating conditions for synergy amongst management researchers through their collaborative efforts to inform research investment in high-priority areas of national policy. AIM was established in order to increase significantly the contribution of, and future capacity for, world-class UK management research. In specific terms this means supporting research that will identify actions to enhance the UK’s international competitiveness (with the public services having a key role in this as explained later); to raise the quality and international standing of UK research on management, to expand the size and capacity of the active UK research base on management; and to engage with practitioners and other users of research within and beyond the UK as co-producers of knowledge about management. AIM, within the UK, consists of 289 Fellows, of whom 11 are Public Service Fellows, 41 Research Fellows and 62 Scholars. There are also 74 International Visiting Fellows attached to the AIM network